Water-soluble naphthalimide-based 'Pourbaix sensors': pH and redox-activated fluorescent AND logic gates based on photoinduced electron transfer. (30th August 2016) - Johnson, Alex D.; Paterson, Kyle A.; Spiteri, Jake C.; Denisov, Sergey A.; Jonusauskas, Gediminas; Tron, Arnaud; McClenaghan, Nathan D.; Magri, David C.
Abstract : Naphthalimide-based 'Pourbaix sensors' for redox potential and pH fluoresce with a lifetime of 8.5 ns while photoinduced electron transfer occurs on a time scale of 20 ps. Abstract : Two novel naphthalimide-based 'Pourbaix sensors' for redox potential and pH were designed based on a 'fluorophore–spacer1 –receptor–spacer2 –electron-donor' configuration. The synthesised molecular logic gates consist of an alkylated 1, 8-naphthalimide fluorophore connected to a tertiary amine by a flexible ethylene spacer to a ferrocene moiety via a methylene spacer. The UV-visible absorption and steady state fluorescent properties were examined in methanol and 1 : 1 (v/v) methanol/water. The spectroscopic properties are modulated by internal charge transfer (ICT) and photoinduced electron transfer (PET) mechanisms. A log β H + of 9.2 and 8.7 were determined in 1 : 1 (v/v) methanol/water for the methylated1 and butylated2 compounds, respectively. An apparent log β Fe 3+ of 4.2 was determined in 1 : 1 (v/v) methanol/water at pH 4. Time-resolved spectroscopic studies elucidated the stimulus-modulated photoinduced electron transfer pathways. In the oxidised and protonated state, 1 exhibits a single fluorescence lifetime of 8.5 ns, while an efficient photoinduced electron transfer characterised by a time constant of 20 ps is revealed by femtosecond transient absorption spectroscopy in the absence of a perturbing stimulus.